Quantitative and qualitative features of carotid and coronary atherosclerotic plaque among men and women - Onnis, Carlotta; Cadeddu Dessalvi, Christian; Cademartiri, Filippo; Muscogiuri, Giuseppe; Angius, Simone; Contini, Francesca; Suri, Jasjit S.; Sironi, Sandro; Salgado, Rodrigo; Esposito, Antonio; Saba, Luca (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVDs), particularly ischemic heart disease (IHD) and stroke, present epidemiologically in a different way among sexes. The reasons of these sex-based differences should be delved into sex-specific cardiovascular (CV) risk factors and different mechanisms of atherosclerotic progression. Imaging techniques of both carotid and coronary atherosclerotic plaques represent a tool to demonstrate sex-related features which might be used to further and better assess CV risk of male and female population. The aim of this review is to evaluate current knowledge on sex-specific qualitative and quantitative plaque features of coronary and carotid atherosclerosis. We also discuss the clinical implication of a sex-based plaque phenotype, evaluated with non-invasive imaging techniques, such as CT-angiography and MRI-angiography, to stratify CV risk.